Overview of the Successful Implementation of Electronic Medical Records at the Otanaha Regional General Hospital (RSUD) - Widya Waty M. Danial; Herlina Jusuf; Tri Septian Maksum (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Electronic Medical Record (RME) is a digital system that aims to improve the efficiency, accuracy, and quality of health services in hospitals. The Government of Indonesia requires all health facilities, including Otanaha Hospital, to implement RME according to the latest regulations. This study aims to describe the success of the implementation of RME at Otanaha Hospital.A type of descriptive research with quantitative methods. A sample of 113 health workers and administrative staff was selected proportionally simple random. Data were collected through questionnaires and interviews, analyzed descriptively. The results of the study showed that the implementation of RME at Otanaha Hospital was considered very good by the majority of users. The quality of RME information is considered adequate and supports clinical services. Management support is strong and contributes to the success of implementation. Users are considered ready and receive effective training, supported by good infrastructure. The satisfaction level is still low, it needs to improve the content, convenience, and speed of the system. The implementation of RME is considered to have not been successful because the efficiency and quality of service have not been optimal. The RME at Otanaha Hospital is good enough, but it needs to improve infrastructure and improve human resource training so that the use of RME is more optimal. Evaluation and development of sustainable systems are important to support the quality of health services.